In vitro assays identified thiohydantoins with anti-trypanosomatid activity and molecular modelling studies indicated possible selective CYP51 inhibition - Priscila Goes Camargo; Helena Tiemi Suzukawa; Patrícia Morais Lopes Pereira; Mariana Luiza Silva; Fernando Macedo Jr; Magaly Girão Albuquerque; Carlos Rangel Rodrigues; Sueli Fumie Yamada-Ogatta; Camilo Henrique da Silva Lima; Marcelle de Lima Ferreira Bispo (Scientific Reports)
Abstract This work investigates the anti-trypanosomal activities of ten thiohydantoin derivatives against the parasite Trypanosoma cruzi. Compounds with aliphatic chains (THD1, THD3, and THD5) exhibited the most promising IC50 against the epimastigote form of T. cruzi. Also, it showed lower cytotoxicity to mammalian cells. THD3 and THD5 (IC50 = 72.4 µg/mL and 115 µg/mL) presented great activity against trypomastigote and amastigote forms (IC50 = 47.7 µg/mL and 34.1 µg/mL). THD5 had high selectivity index (SI = 15.1) against the amastigote form. The molecular docking and molecular dynamics simulations were performed to understand the interaction between the THD and the important target CYP51 enzyme essential to T. cruzi. THD3 and THD5 were found to have strong interactions within the hydrophobic channel of CYP51 due to their aliphatic side chains, leading to favorable binding free energies. Despite the possibility of cross-reactivity between THD5 and human CYP2C9, the results indicate low identity and similarity between the homolog enzymes and possible selectivity of THD5 for the protozoan one, suggesting that these compounds could inhibit sterol biosynthesis, crucial for the parasite’s survival​. These findings indicate that THD3 and THD5 are promising hits for the development of Chagas disease treatments. To fully validate this potential, carrying out enzymatic and other in vitro and in vivo assays is essential in the future.